The Construction of A Family Communication Relationship in the Digital Era in Order to Create A Happy, Loving and Supportive (Sakinah, Mawaddah, Warohmah) Family - Asmaya, Enung (International Conference of Moslem Society, 2018)
Family communication relationship is an important component to achieve ideal Islamic family goals as a sakinah, mawaddah, warohmah (samara) or a happy, loving and supportive family in this digital era. Since the relation within the family has a huge effect to shape those family goals; without a relevant communication, especially in this digital era, the relation can be disruptive and the family goals can be utterly unattainable. Therefore, that issue became the main reason why this subject was crucial to be investigated and reviewed. Critics-constructive analysis towards several books and journals was conducted in order to construct a family communication relationship to be suitable with the family goals in this emergence of turbulence digital era. In the end, the results of this study showed that the construction of equal – and polite – relationship, with the consensual-traditional type of relationship was accepted.